The Role of Gut Microbiota in Neurodegenerative Diseases - Porwolik, Hanna; Porwolik, Agnieszka; Bodera, Magdalena; Szydłowski, Radosław; Porwolik, Agata; Skrzypiec, Barbara; Hamerla, Anna; Kaźmierska, Anna; Gawron, Julia (Journal of Education, Health and Sport, 2025)
Introduction: The gut microbiota is a key component of the gut-brain axis, and its dysbiosis promotes neuroinflammation. The microbiome plays a significant role in the pathogenesis of neurodegenerative diseases. This article focuses on Alzheimer’s and Parkinson’s diseases. Materials and methods: PubMed and Google Scholar databases were searched using the keywords: "gut microbiota," "neurodegenerative diseases," "probiotics," and "fecal microbiota transplantation." A selection of relevant materials was then analyzed. Aim of the study: The aim of this study is to investigate the impact of the gut microbiota on the development of neurodegenerative diseases, with a particular focus on Parkinson’s and Alzheimer’s, and to explore the possibility of slowing their progression or improving their treatment by subjecting the microbiota to change. Description of the state of knowledge: Targeting the gut microbiota represents a novel avenue for managing NDDs. Therapeutic strategies focusing on microbiota modulation, including probiotics and FMT, show significant potential. Further research is essential to validate these approaches and optimize personalized treatments for AD and PD. Results: Gut microbiota dysbiosis was found to significantly contribute to the progression of AD and PD diseases by promoting neuroinflammation, disrupting the blood-brain barrier, and altering neurotransmitter levels. Probiotics, particularly Lactobacillus and Bifidobacterium strains and FMT showed potential in restoring microbial balance and reducing inflammation and improved cognitive and motor functions. Despite these promising findings, clinical evidence remains limited, and further research is necessary.